The Strategic Role of Muslim Women's Leadership in Advancing Education: an Analysis from an Islamic Perspective - Anggie Sri Utari; Fahrur Rozy; M. Agil Febrian; Misra Nova; Siti Qomariah; Ali Imran Sinaga (Tasqif: Journal of Islamic Pedagogy, 2024)
At present, it is clear that leadership roles are increasingly being held by women. For instance, in the field of education, numerous women occupy key positions, such as principals, deans, and even rectors. This trend aligns with the women's emancipation movement and the gender equality movement, which advocate for equal rights for women in various aspects of life. The purpose of this study is to explore the meaning and characteristics of leadership, including leadership styles and roles, principles and laws governing women's leadership, the impact of women's leadership in education, and the significance of women's leadership within Islam. Moreover, this research employs a qualitative methodology utilizing a library research approach. A library study is a type of research that relies on a variety of reading materials, such as books and journal articles, as references. This research highlights that women are no longer perceived as weak; they consistently demonstrate their strength above and beyond societal expectations, increasingly taking on prominent leadership roles. Furthermore, it posits that when a woman assumes a role such as a principal, office head, or class leader, especially within the educational sector, she should embody fairness, honesty, and responsibility in her leadership.